Sosialisasi Pengembangan Pembelajaran Berbasis Masalah Berbantuan Geogebra Meningkatkan Kemampuan Berpikir Kritis di SMP 1 Parulian Medan - Panjaitan, Hendrikson; Binnner Sihaloho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This community service aims to: (1) Provide education and training regarding Geogebra-assisted learning development to training participants (teachers), (2) Increase motivation and good mental attitude, to develop their own teaching modules. This community service was carried out at SMP1 Parulian Medan. The partner in this activity is SMP Parulian 1 Medan. The methods in this community service are: (1) Analyzing the situation and needs, (2) After analyzing the situation and needs, the next step is to set PKM objectives, (3) Designing training, mentoring and workshop models, (4) Expert validation, (5) Implementation, (6) Evaluation The results of this activity include: (1) the participants understand and can create teaching materials in the form of modules, worksheets, (2) the participants' motivation to create their own teaching modules increases.